2008
DOI: 10.1016/j.visres.2008.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Expectancies modulate attentional capture by salient color singletons

Abstract: In singleton feature search for a form-defined target, the presentation of a task-irrelevant, but salient singleton color distractor is known to interfere with target detection [Theeuwes, J. (1991). Cross-dimensional perceptual selectivity. Perception & Psychophysics, 50, 184-193; Theeuwes, J. (1992). Perceptual selectivity for color and form. Perception & Psychophysics, 51, 599-606]. The present study was designed to re-examine this effect, by presenting observers with a singleton form target (on each trial) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
119
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(142 citation statements)
references
References 17 publications
22
119
1
Order By: Relevance
“…These results are consistent with previous findings showing that an infrequently presented salient distractor in visual search continues to interfere with search performance (e.g., Geyer, Müller, & Krummenacher, 2008). Consistent previous empirical work (Asplund et al, 2010;Horstmann, 2002Horstmann, , 2005Horstmann, , 2006Kazmerski & Friedman, 1995;Retell et al, 2015;Schűtzwohl, 1998) and theoretical accounts of surprise and novelty (Meyer et al, 1997;Sokolov, 1963;Sokolov & Vinogradova 1975), this interference dissipated as a function of exposure to the motion cue in all four conditions (see Fig.…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with previous findings showing that an infrequently presented salient distractor in visual search continues to interfere with search performance (e.g., Geyer, Müller, & Krummenacher, 2008). Consistent previous empirical work (Asplund et al, 2010;Horstmann, 2002Horstmann, , 2005Horstmann, , 2006Kazmerski & Friedman, 1995;Retell et al, 2015;Schűtzwohl, 1998) and theoretical accounts of surprise and novelty (Meyer et al, 1997;Sokolov, 1963;Sokolov & Vinogradova 1975), this interference dissipated as a function of exposure to the motion cue in all four conditions (see Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Recent findings suggest that this is a plausible explanation (Folk & Remington, 2007;Geyer, Müller, & Krummenacher, 2008;Müller, Geyer, Zehetleitner, & Krummenacher, 2009;Neo & Chua, 2006). For example, Folk and Remington (2007) had participants search for a colour target and presented a colour or onset cue prior to each target.…”
Section: Discussionmentioning
confidence: 99%
“…However, if participants were adopting a colour singleton set and motion captured attention due to its infrequent presentation (Folk & Remington, 2007;Geyer, Müller, & Krummenacher, 2008;Müller, Geyer, Zehetleitner, & Krummenacher, 2009;Neo & Chua, 2006), then the cueing effect produced by motion cues should be reduced or eliminated in Experiment 2.…”
Section: Methodsmentioning
confidence: 99%
“…Yet, target-similar onset distractors (e.g., onsets with the same colour as the target) typically attract the gaze more strongly (e.g., on 49 % of all trials) than targetdissimilar onset distractors (e.g., green onsets; 7 %: see Ludwig & Gilchrist, 2002, Experiment 1). These results suggest that capture by irrelevant onsets is modulated by topdown processes (Becker & Lewis, 2015;Geyer, Mueller & Krummenacher, 2008;Ludwig & Gilchrist, 2002;Moher et al, 2011, Sayim et al, 2010Wu & Remington, 2003). Critically, however, Mulckhuyse and colleagues (2008) compared the time-course of saccades to target-similar and dissimilar onsets with a cumulative latency distribution analysis, and found that saccades to the target-similar onset did not start earlier, as one would expect on a feedforward account (where target-similar items should enjoy a selection advantage).…”
mentioning
confidence: 97%